DNA amplification, optimization and cloning of several target genes from Burkholderia pseudomallei - Osman, Abdul Latif; Syed Abdullah, Syed Mohamed; Drahaman, Siti Marhamah; Raih, Mohd Firdaus; Muhamad Bunnori, Noraslinda; Mohamed Rehan, Aisyah (Universiti Teknologi Malaysia, 2015)
Burkholderia pseudomallei is a saprophytic Gram-negative bacillus that is found in soil and surface water. It causes the disease melioidosis, which infect humans and animals. Melioidosis can be fatal in human, where it causes fever and commonly present with pneumonia, with or without septicaemia. Melioidosis is primarily endemic in Southeast Asia and Northern Australia, but has also been found in the Middle East, China and South America. It is challenging to treat melioidosis, as it is intrinsically resistant to many antibiotics, and can cause latent infection. By characterizing identified protein targets from B. pseudomallei, we can gain fundamental knowledge on how this bacterium behaves, and thus provide us strategies to combat them. We report here the recent progress of DNA amplification and cloning of four target genes from B. pseudomallei strain D286 performed in Kulliyyah of Science, IIUM. Genomic DNA of B. pseudomallei strain D286 is obtained from School of Biosciences & Biotechnology, UKM. The four target genes; BPSL1612, BPSL1618, BPSL1691 and BPSL2054 were chosen from 52 hypothetical proteins predicted to be essential in B. pseudomallei by transposon-directed insertion site sequencing (TraDIS) technique (Moule et al., 2014). All four target genes were subjected to nested PCR amplification for subsequent GatewayTM cloning protocols, expression and purification studies.